2019
DOI: 10.1088/1475-7516/2019/11/041
|View full text |Cite
|
Sign up to set email alerts
|

A robust measurement of the first higher-derivative bias of dark matter halos

Abstract: We present a new simulation technique in which any chosen mode k of the density contrast field can be amplified by an amplitude ∆. These amplified-mode simulations allow us to study the response of the halo density field to a long-wavelength mode other than the DC mode. In this sense they are a generalization of the separate-universe simulations to finitewavelength modes. In particular, we use these simulations to obtain robust measurements of the first higher-derivative bias of dark matter halos b ∇ 2 δ . We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 51 publications
1
38
1
Order By: Relevance
“…Note that a recent study [34] has found some deviations from this scaling. Now let us discuss the redshift space counterterms, which are dominated by the fingers-of-God effect.…”
Section: Parameter Definition Fiducial Value Hmentioning
confidence: 74%
See 1 more Smart Citation
“…Note that a recent study [34] has found some deviations from this scaling. Now let us discuss the redshift space counterterms, which are dominated by the fingers-of-God effect.…”
Section: Parameter Definition Fiducial Value Hmentioning
confidence: 74%
“…As for the higher-derivative bias coefficient, the measurements from N-body simulations [34,78,101] suggest that it is an order-one quantity in units of [Mpc/h] 2 . Thus, we adopt the following fiducial value along with the time-dependence that corresponds to the one-loop contribution,…”
Section: Parameter Definition Fiducial Value Hmentioning
confidence: 99%
“…In general, this expansion is controlled by the parameter (kR * ) 2 , where k is the wavenumber and R * is a spatial length scale that is specific to a given tracer. For halos, this scale is expected and found to be of order the Lagrangian radius [5,45,46], but for real galaxies it could be substantially larger (e.g., [47][48][49]), so that the ability to include higher-derivative bias operators is potentially important. Even for halos, Ref.…”
Section: Higher-derivative Biasmentioning
confidence: 99%
“…Several measurements of the effective sound speed have been presented in the literature [4,46,[59][60][61], most of which have been based on Eulerian perturbation theory. The closest comparison point is offered by [4].…”
Section: Lptmentioning
confidence: 99%
“…If the scale R * is larger than the spatial length scale (nonlinear scale) controlling the perturbative expansion, then one can correspondingly include higher-order derivative terms. This might be the case for very massive halos [66][67][68], for example, or due to radiative-transfer effects [69][70][71][72][73][74].…”
Section: Higher Derivativesmentioning
confidence: 99%